2014
DOI: 10.1016/j.mad.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Ageing-related responses to antiangiogenic effects of sunitinib in atherosclerosis-prone mice

Abstract: Abbreviations: LLC -Lewis lung carcinoma; MVD -microvascular density; CAIX -carbonyl anhydrase IX 2 AbstractAntiangiogenic therapies in cancer exert their effects in the context of age-related comorbidities, which affect the entirety of the vascular system. Among those conditions, the impact of atherosclerosis is especially prevalent, but poorly understood, and not reflected in mouse models routinely used for testing antiangiogenic therapeutics. Our earlier work suggested that these obstacles can be overcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Whilst this provides functional and mechanistic evidence for age-impaired wound healing and ischemia-mediated angiogenesis, the key triggers for these events have not been entirely elucidated. Recent data also indicate that processes fundamental to aging also play pivotal roles in cardiovascular disease associated with advanced age [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Whilst this provides functional and mechanistic evidence for age-impaired wound healing and ischemia-mediated angiogenesis, the key triggers for these events have not been entirely elucidated. Recent data also indicate that processes fundamental to aging also play pivotal roles in cardiovascular disease associated with advanced age [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Other authors have shown that knockdown of RBP4 significantly reduces ovarian cancer cell migration and proliferation driven through the RhoA/Rock1 and extracellular signal-regulated kinase (ERK) pathways [26].The aim of our studies was to explain the role of RBP4 protein in the growth and metastatic spread of two murine breast cancer isogenic cell lines (derived from a single tumor of BALB/c mouse); metastatic 4T1 and nonmetastatic 67NR, representing basal-like and luminal-like phenotype, respectively [2,4]. Moreover, because, in many cases, cancer is associated with the aging process (largely reviewed in [27]) and aging affects the metastatic phenotype of cancer cells as well as tumor angiogenesis [28][29][30], we decided to include in our studies young and aged animals. To the best of our knowledge, no previous studies have investigated the effect of RBP4 protein on the metastatic spread of cancer.…”
mentioning
confidence: 99%
“…Moreover, impairment of angiogenesis is described to be the cause of slower cancer growth in the elderly [3]. Further, tumour responsiveness to therapeutic agents differs in young and old animals [3,4]. Despite this evidence, the overwhelming majority of research focusing on the antitumour activity of various compounds is carried out on young animals.…”
mentioning
confidence: 99%